ETL Data Warehouse Pada Sistem Monitoring Besaran Listrik Menggunakan Protokol Modbus TCP - Ferdianto Tangdililing; Stefany Yunita Bara'langi (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2016)
This research aims design ETL in data warehouse as a storage of data logging. The source of data warehouse can be diverse both in terms of data storage structure, platform, device and user interface so-called syntactic heterogeneity. Modelling data in this research using a snowflake schema because the data involved is already 3rd Normal Form. This application is powered by software applications built using LabView tools and sensors Schneider 810 power meter will read the input data. The results obtained in this research are ETL can build a data warehouse for the storage of data logging despite syntactic heterogeneity.